Are there clinical and subclinical/pathological forms of Paget’s disease of the breast? - Pelorca, Rafael José Fábio; de Oliveira-Junior, Idam; Vieira, René Aloisio da Costa (Frontiers in Oncology, 2023)
Introduction Breast disease management has changed over recent decades, related to molecular subtype, oncoplastic surgery and targeted therapies. Nevertheless, literature on Paget’s disease of the breast (PDB), initially described as a clinical entity and now considered a multifocal/multicentric disease. Methods PDB was classified as clinical in the presence of areolar abnormalities and as subclinical/pathological in all other cases. Clinical and prognostic data were evaluated and compared between the different presentation forms. Statistics comprised descriptive analysis, inter-group comparison (chi-square and Mann-Whitney tests) and overall and cancer-specific survival rates (Kaplan-Meier method and the log-rank test). Results Of 85 patients included in this series, PDB was clinical in 58.8%. Overall, 27.1% had stage 0 and 92.9% had multifocal/multicentric disease. Most patients (83.5%) had the HER2 or luminal HER2 molecular subtype. Patients with clinical PDB had a higher rate of in situ disease (p=0.028) and were more likely to undergo breast-conserving surgery (p<0.001). Most of the 43 patients with HER2 invasive disease received anti-HER therapy. Mean follow-up time was 71.2 ± 43.3 months. Cancer-specific actuarial survival at 60 and 120 months was 92.3% and 83.1%, respectively. Survival was unaffected by the clinical form of PDB (p=0.275), anti-HER therapy (p=0.509) or oncoplastic surgery (p=0.821). Conversely, clinical stage affected survival significantly (p ≤ 0.001). Conclusion PDB is a rare condition associated with multifocality/multicentricity and HER2 overexpression. Cases of clinical disease and those of subclinical/pathological disease differ significantly. Further studies are required to evaluate the clinical/areolar disease and the impact of advances in breast disease management on PDB.